Methane production and nutritional content from the diet consumed by grazing cattle - García, Elizabeth; Herrera, Esperanza; Murillo, Manuel; Jiménez, Rafael; Sierra, Daniel; Pámanes, Gerardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 1970)
It is a high priority to account for methane emissions from cattle grazing grasslands in order to evaluate the strategies for mitigating GHG emissions in livestock. The aim of this study was to evaluate in vitro ruminal methane production and nutritional content of the consumed diet by bovines grazing an open medium grassland in atypical dry and rainy periods in the semi-arid region of the state of Durango, Mexico. Four rumen fistulated bovines were subjected of an ad libitum graze under a repeated measure design. Chemical analysis showed that DM, OM, NDF and ADF increased in rainy period (p<0.05). Otherwise, CP, EE, phosphorus contains and IVDMD increased in dry period (p<0.05). Ruminal fermentation parameters as pH and volatile fatty acids as acetic, propionic and butyric, showed no changes among periods (p>0.05). However, ammonia increased in rainy period (p<0.05). Moreover, gas production kinetics only showed differences in lag phase (p<0.05); whereas, maximum gas production and production constant rate showed no changes among periods (p>0.05). Likewise, methane production showed no changes among both periods (p<0.05). As conclusion, it is observed that nutritional quality of the consumed diet by bovines grazing and open medium grasslands in dry and rainy periods presents acceptable protein values (8-10 %). In addition, phosphorus contents are higher than the minimum requirements for growing bovines. Furthermore, methane production was not affected by dry and rainy periods.